2020
DOI: 10.1186/s13058-020-01313-7
|View full text |Cite
|
Sign up to set email alerts
|

BRCAness digitalMLPA profiling predicts benefit of intensified platinum-based chemotherapy in triple-negative and luminal-type breast cancer

Abstract: Background: We previously showed that BRCA-like profiles can be used to preselect individuals with the highest risk of carrying BRCA mutations but could also indicate which patients would benefit from double-strand break inducing chemotherapy. A simple, robust, and reliable assay for clinical use that utilizes limited amounts of formalin-fixed, paraffin-embedded tumor tissue to assess BRCAness status in both ER-positive and ER-negative breast cancer (BC) is currently lacking. Methods: A digital multiplex ligat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
(72 reference statements)
0
7
0
Order By: Relevance
“…The sensitivity ranged from 53% to 100%, and the specificity ranged from 40% to 100%. The HRD test with the highest sensitivity and corresponding specificity was HRD-DNA [43], followed by BRCA1-like digitalMLPA classifier [36], BRCA1 classifier [22], ShallowHRD [35], BRCA1-like MLPA classifier [23], DNA-methylation-based RF classifier [38], and BRCA2 classifier [24]. The HRD score [16], LST [7], BRCA1ness signature [29], and Ovarian cancer BRCA1-like classifier [40] had high sensitivity, but the corresponding specificities were relatively low (Figure 4).…”
Section: Hrd Test Performancementioning
confidence: 99%
“…The sensitivity ranged from 53% to 100%, and the specificity ranged from 40% to 100%. The HRD test with the highest sensitivity and corresponding specificity was HRD-DNA [43], followed by BRCA1-like digitalMLPA classifier [36], BRCA1 classifier [22], ShallowHRD [35], BRCA1-like MLPA classifier [23], DNA-methylation-based RF classifier [38], and BRCA2 classifier [24]. The HRD score [16], LST [7], BRCA1ness signature [29], and Ovarian cancer BRCA1-like classifier [40] had high sensitivity, but the corresponding specificities were relatively low (Figure 4).…”
Section: Hrd Test Performancementioning
confidence: 99%
“…For patients with breast, ovarian, and pancreatic cancers harboring BRCA alterations, PARP inhibitors are used after chemotherapy. BRCA mutations predict the response of ovarian and breast cancers to platinum (51,52). Niraparib and olaparib are recommended as maintenance therapies after platinumbased chemotherapy only for platinum-sensitive cancer (53)(54)(55).…”
Section: Platinum Sensitivity Could Be a Biomarker For Efficacy Of A Parp Inhibitormentioning
confidence: 99%
“…Moreover, g BRCA1 m or BRCA1 -like tumors often present with aggressive phenotypes [ 22 , 23 ] and are hypothesized to be associated with a worse prognosis compared to germline BRCA1 wild-type (g BRCA1 wt) or non- BRCA1 -like tumors. However, many studies observed that in chemotherapy-treated TNBC patients, those with g BRCA1 m or BRCA1 -like tumors had equivalent or even better survival compared to those with g BRCA1 wt or non- BRCA1 -like tumors [ 5 , 6 , 24 27 ]. This suggests that chemotherapy might obscure the worse survival of patients with g BRCA1 m or BRCA1- like tumors [ 28 ].…”
Section: Introductionmentioning
confidence: 99%